Emerging Options for Emergency Contraception - Koyama, Atsuko (Libertas Academica, 2013)
Emergency post-coital contraception (EC) is an effective method of preventing pregnancy when used appropriately. EC has been available since the 1970s, and its availability and use have become widespread. Options for EC are broad and include the copper intrauterine device (IUD) and emergency contraceptive pills such as levonorgestrel, ulipristal acetate, combined oral contraceptive pills (Yuzpe method), and less commonly, mifepristone. Some options are available over-the-counter, while others require provider prescription or placement. There are no absolute contraindications to the use of emergency contraceptive pills, with the exception of ulipristal acetate and mifepristone. This article reviews the mechanisms of action, efficacy, safety, side effects, clinical considerations, and patient preferences with respect to EC usage. The decision of which regimen to use is influenced by local availability, cost, and patient preference.